Controlling Electrical Appliances using Bluetooth & J2ME-enabled Mobile Phone - Md. Ridzuan, Redza Shafique (Universiti Teknologi PETRONAS, 2007)
This project focuses on the development of a universal remote control system that utilizes the use of Bluetooth and Java technology on mobile phones in controlling electrical appliances. The remote control does not confine to the physical barriers that are normally found at home like the typical IrDA remote controls. The system suggests the usage of Bluetooth technology in order to solve and expand the capability of the IrDA remote control technology that is still being widely used. This is also due to the fact that almost all electrical devices and appliances come with their own proprietary remote control. By having a universal remote control, it is possible to eliminate the need for such many remote controls at home. From the client application point of view, the user interface is constructed using Java 2 Mobile Edition as it is being supported by many mobile phones instead of other of different architectures. From the mobile phone, users are able to connect to the Bluetooth server that then interacts with the circuit where the electronic components reside. Immediate direct manipulation of the circuit is crucial as remote control system is one of the real time systems and it needs to be updated as soon as the state of appliances is modified. As a result, this project was developed using Bluez in Linux, for the server part; and Nokia 6230 Series 40 cell phone for the client application. In a nutshell, the end product gives flexibility to the users by promoting the usage of their mobile phones as a universal remote control for their electrical appliances.